2015
DOI: 10.1186/s12885-015-1469-5
|View full text |Cite
|
Sign up to set email alerts
|

Intratumor cholesteryl ester accumulation is associated with human breast cancer proliferation and aggressive potential: a molecular and clinicopathological study

Abstract: BackgroundThe metabolic effect of intratumor cholesteryl ester (CE) in breast cancer remains poorly understood. The objective was to analyze the relationship between intratumor CE content and clinicopathological variables in human breast carcinomas.MethodsWe classified 30 breast carcinoma samples into three subgroups: 10 luminal-A tumors (ER+/PR+/Her2-), 10 Her-2 tumors (ER-/PR-/Her2+), and 10 triple negative (TN) tumors (ER-/PR-/Her2-). We analyzed intratumor neutral CE, free cholesterol (FC) and triglyceride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
161
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(166 citation statements)
references
References 47 publications
3
161
1
1
Order By: Relevance
“…The metabolic effect of CE in breast cancer remains poorly understood. But the relationship between CE and poor clinical outcome in human breast cancer has been reported [40]. These studies have indicated that these selected lipid species could be classified as biomarkers for the diagnosis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic effect of CE in breast cancer remains poorly understood. But the relationship between CE and poor clinical outcome in human breast cancer has been reported [40]. These studies have indicated that these selected lipid species could be classified as biomarkers for the diagnosis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…1, 2 Evidence suggests a major role for lipids in the progression of hematological 35 and other malignancies 610 with specific involvement of cholesterol and cholesteryl esters, along with the high-density lipoproteins (HDL) that carry them. 1114 In the case of B-cell lymphoma, B-cell receptor (BCR) signaling, including low level, tonic signaling observed in germinal center (GC)-derived diffuse large B cell lymphoma (DLBCL) and chronic active signaling in activated B-cell (ABC) DLBCL, has been shown to directly promote cholesterol biosynthesis through intermediate kinases downstream of the BCR to maintain cell membrane integrity and BCR signaling.…”
Section: Introductionmentioning
confidence: 99%
“…As the most important mediator in HDL-cholesterol metabolism, SR-B1 has been reported in several cancers. 10,11,13,15 Nevertheless, we knew little about the roles of SR-B1 in ccRCC. In our study, we explored the expression of SR-B1 in ccRCC tissues and found that SR-B1 expression was much higher in cancerous tissues compared with their normal counterparts.…”
Section: Discussionmentioning
confidence: 99%